Flow-controlled ventilation during ear, nose and throat surgery: A prospective observational study. Issue 5 (May 2019) - Schmidt, Johannes; Günther, Franziska; Weber, Jonas; Wirth, Steffen; Brandes, Ivo; Barnes, Tom; Zarbock, Alexander; Schumann, Stefan; Enk, Dietmar
Abstract : BACKGROUND: Flow-controlled ventilation (FCV) is a new mechanical ventilation mode that maintains constant flow during inspiration and expiration with standard tidal volumes via cuffed narrow-bore endotracheal tubes. Originating in manually operated 'expiratory ventilation assistance', FCV extends this technique by automatic control of airway flow, monitoring of intratracheal pressure and control of peak inspiratory pressure and end-expiratory pressure. FCV has not yet been described in a clinical study. OBJECTIVE: The aim of this study was to provide an initial assessment of FCV in mechanically ventilated patients undergoing ear, nose and throat surgery and evaluate its potential for future use. DESIGN: An observational study. SETTING: Two German academic medical centres from 24 November 2017 to 09 January 2018. PATIENTS: Consecutive patients (≥ 18 years) scheduled for elective ear, nose and throat surgery. Exclusion criteria were planned laser surgery, intended fibreoptic awake intubation, emergency procedures, increased risk of aspiration, American Society of Anesthesiologists (ASA) physical status more than III and chronic obstructive pulmonary disease classified as GOLD stage more than II. INTERVENTION: Peri-operative use of FCV provided by a new type of ventilator (Evone) via a narrow-bore endotracheal tube (Tritube). MAIN OUTCOME MEASURES: Minute volume, respiratory rate, intratidal tracheal pressure amplitude (Δ p ) and end-tidal CO2 ( P et CO2 ) were recorded every 5 min. All adverse events were noted. Data are presented as median [IQR]. RESULTS: Sixteen patients provided 15 evaluable data sets. A minute volume of 5.0 [4.4 to 6.4] l min −1 and a respiratory rate of 9 [8 to 11] min −1 generated a P et CO2 of 4.9 [4.8 to 5.0] kPa. Δ p was 10 [9 to 12] cmH2 O. Five adverse events were recorded: a tube obstruction due to airway secretions and four tube dislocations (two attributed to coughing, two not study-related). CONCLUSION: FCV achieves adequate P et CO2 levels with minute volume and Δ p in the normal range. Tritube's high flow resistance may increase the likelihood of tube dislocations if the patient coughs. Although further evaluation is necessary, FCV provides a new option for short-term mechanical ventilation. The successful operation of FCV with narrow-bore tubes contributes to the armamentarium for airway management. TRIAL REGISTRATION: DRKS00013312 Abstract : Supplemental Digital Content is available in the text